(3GdeSFhdjI GdeOfjI GdfGTFI Yf GjhGA GdSjGQGJ (B: s (3OQGSI ebGQfI (B/ s - (3eMeO MSfjf YHOGdYGWi MSfjfs; (3YHOGdQTjO eGehf TOjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3de jfXe GdeTQY GdeUQi Gh GdaQfSi ehVhY GjhGA GdSjGQGJ JfXjeG bGfhfjG cGedG hde jJfHg Gdi Gf GdJRGe UGMH GdLQGL jRjO Yf GdJRGe MGQS GdGTjGA agh HGdGVGaI Gdi GdJRGeg HMQGSI GdSjGQI jdJRe HMaX GdSjGQI MJi dGJJda Gh jUjHgG VQQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2006s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B537-579s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdeTQY GdeUQis; (3GjhGA GdSjGQGJs; (3UGMH GdLQGLs; (3GdSjGQGJs; (3YbO GdLQGLs; (3GdSjGQI GdeSQhbIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs